Restrictive versus standard IV fluid therapy in adult ICU patients with septic shock-Bayesian analyses of the CLASSIC trial - Sivapalan, Praleene; Meyhoff, Tine Sylvest; Hjortrup, Peter Buhl; Lange, Theis; Kaas-Hansen, Benjamin Skov; Kjaer, Maj-Brit N; Laake, Jon Henrik; Cronhjort, Maria; Jakob, Stephan M; Cecconi, Maurizio; Nalos, Marek; Ostermann, Marlies; et al. (Acta anaesthesiologica Scandinavica, 2024)
BACKGROUND: The CLASSIC trial assessed the effects of restrictive versus standard intravenous (IV) fluid therapy in adult intensive care unit (ICU) patients with septic shock. This pre-planned study provides a probabilistic interpretation and evaluates heterogeneity in treatment effects (HTE). METHODS: We analysed mortality, serious adverse events (SAEs), serious adverse reactions (SARs) and days alive without life-support within 90 days using Bayesian models with weakly informative priors. HTE on mortality was assessed according to five baseline variables: disease severity, vasopressor dose, lactate levels, creatinine values and IV fluid volumes given before randomisation. RESULTS: The absolute difference in mortality was 0.2%-points (95% credible interval: -5.0 to 5.4; 47% posterior probability of benefit [risk difference <0.0%-points]) with restrictive IV fluid. The posterior probabilities of benefits with restrictive IV fluid were 72% for SAEs, 52% for SARs and 61% for days alive without life-support. The posterior probabilities of no clinically important differences (absolute risk difference ≤2%-points) between the groups were 56% for mortality, 49% for SAEs, 90% for SARs and 38% for days alive without life-support. There was 97% probability of HTE for previous IV fluid volumes analysed continuously, that is, potentially relatively lower mortality of restrictive IV fluids with higher previous IV fluids. No substantial evidence of HTE was found in the other analyses. CONCLUSION: We could not rule out clinically important effects of restrictive IV fluid therapy on mortality, SAEs or days alive without life-support, but substantial effects on SARs were unlikely. IV fluids given before randomisation might interact with IV fluid strategy.
Keywords: randomizované kontrolované studie jako téma; dospělí; jednotky intenzivní péče; Randomized Controlled Trials as Topic; Bayesova věta; lidé; septický šok; tekutinová terapie; Bayes Theorem; Fluid Therapy; Shock, Septic; Adult; Intensive Care Units; Humans